ANALISIS KINERJA TUTOR PADA LEMBAGA PENDIDIKAN NON FORMAL HOME SCHOOLING DI KOTA SEMARANG (Studi pada Pusat Kegiatan Belajar Masyarakat Anugrah Bangsa Semarang) - Susi Sulandari (Departemen Administrasi Publik, Universitas Diponegoro, 2015)
In the Education Law No. 20 of 2003 section five of article 26 of the NonformalEducation noted that non-formal education was held for citizens whorequire educational service that serves as a substitute for, enhancer, and / orcomplement formal education in order to support non-formal education serves todevelop along hayat.Pendidikan potential learners with an emphasis on themastery of knowledge and functional skills and the development of professionalattitude and personality.The results of non-formal education can be appreciated on par with theresults after a formal education program through assessment of equivalency bythe agency designated by the Government or local government with reference tothe national education standardsWhen viewed from the Act Sikdiknas, then the role of non-formal educationis very important to improve the intelligence community and the results of nonformaleducation can be appreciated on par with the results of a formal courseafter going through the process of assessment equalization by the agencydesignated by the Government or local government with reference to the nationaleducation standards.The aim of the study is to examine the performance of tutors on homeschooling in the city of Semarang., To determine the inhibiting factors in theachievement of the performance of tutors on Home Schooling in the city ofSemarang. As well as to provide solutions to overcome obstacles in improvingthe performance of tutors onHome Schooling in SemarangHis research uses descriptive quantitative research methods. By usingprimary and secondary data sources through direct interview by using a list ofclosed and open questions, with source eleventh grade students, tutors, schoolleaders at the Institute of Non-Formal Education Home Schooling Semarang.Analysis of the data used in this study is an average, which is equipped withtables and frequency distribution for the recapitulation equipped with charts.Based on the research results can be concluded that the performance tutoron Pusat Kegiatan Belajar Masyarakat (PKBM) Anugrah Bangsa Semarang isalready well proven by the average number of seven indicators of theperformance figures obtained 3.20 tutors enter both categories.He suggestion in this study was the level of attendance tutor in class inorder endeavored timely, in terms of conveying competence to be achieved inthe plan, there are those who have not submitted, implement contextual learningin order to be improved, there is still a tutor is not maximized in foster activeparticipation of students, still needs to be improved also in response to thepositive participation of students, the use of spoken language properly andsmoothly, and makes a summary by involving students.Keywords: Tutor performance; service; and quality of education